Starting a theatre company : how to become a theatre maker and create your own work - Falconer, Karl (New York : Focal Press, 2023)
Exploring everything from company incorporation and marketing, to legal, finance and festivals, Starting a Theatre Company is the complete guide to running a low-to-no budget or student theatre company. Written by an experienced theatre practitioner and featuring on-the-ground advice, this book covers all aspects of starting a theatre company with limited resources, including how to become a company, finding talent, defining a style, roles and responsibilities, building an audience, marketing, the logistics of a production, legalities, funding, and productions at festivals and beyond. The book also includes a chapter on being a sustainable company, and how to create a mindset that will lead to positive artistic creation. Each chapter contains a list of further resources, key terms and helpful tasks designed to support the reader through all of the steps necessary to thrive as a new organisation. An eResource page contains links to a wide range of industry created templates, guidance and interviews, making it even easier for you to get up and running as simply as possible. Starting a Theatre Company targets Theatre and Performance students interested in building their own theatre companies. This book will also be invaluable to independent producers and theatre makers.
Keywords: Theatrical companies -- Great Britain -- Management; Theater management -- Great Britain